TEACHING MATERIALS IN CREATIVE THINKING SKILLS-BASED LEARNING: A SYSTEMATIC LITERATURE REVIEW - Anwar, Muhamad Khoirul; Suratno; Buroidah, Hikmah; Hasan, M. Ubaidillah (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Teaching materials designed for creative thinking skills are very important because they guide students to develop innovative problem-solving skills and think outside the box. The purpose of this study is to analyze the characteristics of effective teaching materials in supporting creative thinking skills-based learning, and to identify the essential components that must be present in teaching materials to develop these skills. This study is a systematic literature review that describes teaching materials in creative thinking skills-based learning in the field of biology education. This study synthesizes 11 of 42 articles published between 2021–2024 in Sinta 2–4 journals obtained based on the formulation of the problem. The study results consistently demonstrate the dominance and crucial role of digital-based teaching materials in significantly enhancing students' creative thinking skills. These digital resources are uniquely designed with embedded features like multimedia integration, Problem-Based Learning (PBL) scenarios, and open-ended questions, thereby creating a highly interactive, flexible, and relevant learning environment aligned with 21st-century demands. The efficacy of these digital tools is strongly reinforced through their integration with active learning strategies such as PBL and Inquiry-Based Learning, This finding offers significant novelty by providing empirical evidence that locally-adapted digital products are a primary catalyst for pedagogical transformation. The practical implication is that educators must shift their focus from mere information delivery to designing rich learning experiences that explicitly demand students to generate, test, and validate their own creative ideas, preparing them for future complexity.